2022
DOI: 10.1186/s12943-022-01579-9
|View full text |Cite
|
Sign up to set email alerts
|

An EHMT2/NFYA-ALDH2 signaling axis modulates the RAF pathway to regulate paclitaxel resistance in lung cancer

Abstract: Background Lung cancer is a kind of malignancy with high morbidity and mortality worldwide. Paclitaxel (PTX) is the main treatment for non-small cell lung cancer (NSCLC), and resistance to PTX seriously affects the survival of patients. However, the underlying mechanism and potential reversing strategy need to be further explored. Methods We identified ALDH2 as a PTX resistance-related gene using gene microarray analysis. Subsequently, a series of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…[22] Additionally, evidence shows that genes such as paired box 5, aldehyde dehydrogenase 2 family member, and brain abundant membrane attached signal protein 1 are involved in cancer chemotherapy drug resistance. [23][24][25] Although immunotherapy has brought many benefits to patients with different types of cancer, developing a reliable method to identify immune therapy response is of significant clinical importance. [26,27] This study confirms the potential of a TMG-derived HNSCC subtype as an approach for identifying immune therapy response.…”
Section: Discussionmentioning
confidence: 99%
“…[22] Additionally, evidence shows that genes such as paired box 5, aldehyde dehydrogenase 2 family member, and brain abundant membrane attached signal protein 1 are involved in cancer chemotherapy drug resistance. [23][24][25] Although immunotherapy has brought many benefits to patients with different types of cancer, developing a reliable method to identify immune therapy response is of significant clinical importance. [26,27] This study confirms the potential of a TMG-derived HNSCC subtype as an approach for identifying immune therapy response.…”
Section: Discussionmentioning
confidence: 99%
“…186 Wang et al found that the expression of ALDH2 is also upregulated in NSCLC cells, which is associated with cancer cell stemness property and paclitaxel resistance. 187 More implementation is needed to outline a possible role for ALDH2 in cancer.…”
Section: Aldh2mentioning
confidence: 99%
“…Most of these proteins are ATP-driven multidrug efflux pumps such as MDR protein and P-glycoprotein (P-gp). After the intracellular drug binds to the transporter on the cell membrane, ATP hydrolysis drives a conformational change and pushes the drug out of the cell, resulting in the inability of the intracellular drug to accumulate in sufficient quantities to kill the cells [73] . Ruan et al used nanocarriers to reverse drug resistance induced by overexpression of the drug efflux pumps by inhibiting mitochondrial ATP synthesis [52] .…”
Section: Biological Barriersmentioning
confidence: 99%
“…Ruan et al used nanocarriers to reverse drug resistance induced by overexpression of the drug efflux pumps by inhibiting mitochondrial ATP synthesis [ 52 ] . The cyclin-dependent kinase 6-phosphoinositide 3-kinase (CDK6-PI3K) signaling axis is an effective target for attenuating ATP binding cassette subfamily B member 1/P-gp-mediated MDR in cancer cells [ 11 , 74 , 75 ] .…”
Section: Mechanisms Of Tumor Resistancementioning
confidence: 99%
See 1 more Smart Citation